The Paradigm of Constitutionalism: Economic Aspects and Issues of Evaluation - Sargsyan, Hayk; Mkhitaryan, Zhirayr; Nahapetyan, Seda (Bulletin of Yerevan University G: Economics, 2015)
The issues of constitutional economics and theory of public choice, the concept of constitutionalism, its socio-economic cross section are discussed in the article. A brief methodology of evaluation and raising its level from the point of view of management is presented. The applied cognitive and ranking method is one of the modeling tools which is presented without the description of algorithms and software, and the attitudes of its efficiency are a separate issue of research.